Seasonal occurrence and production effects of the biting louse Damalinia limbata on Angora goats and 2 treatment options - L. Brown (Journal of the South African Veterinary Association, 2005)
Adult biting lice Damalinia limbata (Gervais 1844) were most numerous on Angora goats in southwestern Free State Province from November to May with the smallest numbers present during August. Nymphs were most numerous from January to March with the smallest numbers present during July. The largest proportion of adult lice was present on the ventral surface of goats during winter, when population numbers were lowest, and the largest proportion of nymphs during summer, when population numbers were highest. Infestation did not affect the body weight of goats, but adversely affected both the quantity and quality of mohair produced. A single treatment with deltamethrin, applied as a pour-on along the mid-line of the backs of the goats, effectively controlled infestation and resulted in a significant increase in mohair production compared with untreated goats. Deltamethrin sprayed along the sides of the animals was equally effective in controlling infestation.